A Bridge to a Woman's Heart as the Cause of Recurrent Chest Pain: A Case on Myocardial Bridge. (January 2016) - Afzal, Ashwad; Korniyenko, Aleksandr; Haq, Salman
Abstract : Myocardial bridge is a congenital structural variant of the coronary arteries where a segment of the epicardial vessel is surrounded by the myocardium. It is an uncommon entity that may go unnoticed in patients with recurrent chest pain. We present a case on a 36-year-old woman with recurrent chest pain. Initial workup revealed normal routine laboratory test results, cardiac biomarkers, electrocardiogram, and an echocardiogram showing preserved ejection fraction with no valvulopathies. A dobutamine myocardial perfusion stress test was performed; this induced chest pain in the patient with electrocardiogram changes evident for 1-mm ST segment elevation in lead V5 and V6 consistent with myocardial ischemia. Perfusion imaging revealed a small fixed myocardial perfusion defect of the apical inferior wall. A cardiac catheterization revealed moderate-to-severe myocardial bridging involving the middle left anterior descending artery. Treatment with metoprolol and ranolazine resolved her symptoms. This case portrays the importance of recognizing myocardial bridge as the potential cause of recurrent chest pain and its ability to cause myocardial ischemia under stress.